Dislocation activity, stable crack motion, and the warm-prestressing effect in magnesium oxide - Booth, A; Roberts, S; Booth, A; Roberts, S (Wiley, 1994)
Four-point bend tests were performed on precracked single-crystal MgO specimens at different temperatures and strain rates. A large amount of stable crack growth before fracture occurred; etching revealed dislocations in the crack advance region. We believe that dislocation sources near the crack tip emit loops, producing shielding and antishielding dislocations; the latter promote crack advance by a repeated microcleavage mechanism. “Warm-prestressing” experiments, which improve the room-temperature fracture toughness by dislocation shielding, were performed. There was a prestress below which no “warmprestressing effect” (WPSE) was exhibited and the magnitude of the WPSE increased with increasing prestressing temperature.